Parental Influence on Don’s Identity Development: A Psychoanalytic Study Jumbo (2025) - Mahanani, Luberingsih; Herawati, Siane; Purnawati, Maria (Journey: Journal of English Language and Pedagogy, 2026)
This study fills the gap in the analysis of the animated film Jumbo (2025) through a psychoanalytic lens, focusing on how the absence of parents in early life shapes the formation of identity and emotional development in the child character. Using Melanie Klein’s theory as the primary framework to understand how early emotional relationships affect psychological development and Donald Winnicott’s concepts to read the role of the environment that fosters the child, this study employs a descriptive approach by collecting the data through repeatedly viewing the film, followed by analyzing the selected scenes and dialogues. The findings show that the loss of a parent indeed impacts the emotional development of the child. Although it cannot be adequate to be raised by parents, the child will still be able to experience positive emotions without being overly impacted. It is considered this analysis would offer parents new insights into the importance of creating meaningful memories with their children, beyond just being physically, as this can influence the children’s behavior and development as they grow up.